Peran Pengelolaan Kelas dalam Meningkatkan Minat Belajar Pendidikan Agama Buddha dan Budi Pekerti Siswa Kelas VII A SMP Metta Maitreya Pekanbaru - Yadi Sutikno; Dharmaji Chowmas; Suryati; Yanthi Krisna; Linda Yanti (STAB Maitreyawira, 2025)
Based on initial observations, ten students in class VII A of Metta Maitreya Junior High School Pekanbaru have not met the Minimum Completion Criteria (KKM) that has been set. Based on these observations, research will be conducted on how the role of classroom management in increasing the interest in learning Buddhist Religious Education and Budi Pekerti Class VII A Students of Metta Maitreya Junior High School Pekanbaru. Qualitative research methodology will be used. This research will be conducted from December 2024 to March 2025. Metta Maitreya Junior High School located at Jln. T. Tambusai, Komp. Puri Nangka Sari, Pekanbaru, Riau, is the research location. Buddhist Religious Education and Budi Pekerti teachers and students of class VII A of Metta Maitreya Junior High School Pekanbaru, Riau, became the data sources in this research. Data collection techniques used were documentation and interviews. Based on the results of the study, the role of classroom management in increasing the interest in learning Buddhism and Budi Pekerti Education of Class VII A Students of Metta Maitreya Junior High School Pekanbaru is that classroom management plays a role in increasing the interest in learning Buddhism and Budi Pekerti Education of Class VII A of Metta Maitreya Junior High School Pekanbaru. The evidence is from the results of this study which shows that classroom management plays a role in increasing interest in learning Buddhism and Budi Pekerti Education Class VII A Metta Maitreya Junior High School Pekanbaru.